Developmental effects of trichloroacetate in Zebrafish embryos: Association with the production of superoxide anion. Issue 3 (15th November 2018) - Issa, Omar; Hassoun, Ezdihar A.; Williams, Frederick E.
Abstract: To assess the developmental toxicity of trichloroacetate (TCA), zebrafish embryos were exposed to 8 to 48 mM of TCA and evaluated for developmental milestones from 8‐ to 144‐hour postfertilization (hpf). All developmental toxicities are reported in this paper. Embryos were found to have developed edema in response to 16 to 48 mM of TCA exposure at 32‐ to 80‐hpf, experienced delay in hatching success in response to 24 to 48 mM at 80‐hpf. Lordosis was observed in developing embryos exposed to 40 to 48 mM at 55‐ to 144‐hpf. The observed toxic effects of TCA exposure were found to be concentration and exposure period independent. Effects were found to be associated with increases in superoxide anion production, but these increases were also found to be concentration and time independent. TCA resulted in concentration‐dependent increases in embryonic lethality at 144‐hpf, with an LC50 determined to be 29.7 mM.